2019
DOI: 10.3390/horticulturae5030053
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Acetylene Reduction Activities and nifH Genes Associated with Field-Grown Sweet Potatoes with Different Nursery Farmers and Cultivars

Abstract: Sweet potato cultivars obtained from different nursery farmers were cultivated in an experimental field from seedling-stage to harvest, and the acetylene reduction activity (ARA) of different parts of the plant as well as the nifH genes associated with the sweet potatoes were examined. The relationship between these parameters and the plant weights, nitrogen contents, and natural abundance of 15 N was also considered. The highest ARA was detected in the tubers and in September. Fragments of a single type of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The biological nitrogen fixation of plants, rather than by association with microorganisms, can generate crops that are less dependent on synthetic nitrogen fertilizers and can increase agricultural productivity and sustainability [ 50 ]. The sweet potato, the seventh largest food crop in the world [ 2 ], grows well in nitrogen-poor infertile soils, and it is believed that sweet potato endo- and epiphytic microorganisms play important roles in acting upon this growth ability in this plant [ 21 , 22 , 23 , 24 ]. Are these all the reasons?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological nitrogen fixation of plants, rather than by association with microorganisms, can generate crops that are less dependent on synthetic nitrogen fertilizers and can increase agricultural productivity and sustainability [ 50 ]. The sweet potato, the seventh largest food crop in the world [ 2 ], grows well in nitrogen-poor infertile soils, and it is believed that sweet potato endo- and epiphytic microorganisms play important roles in acting upon this growth ability in this plant [ 21 , 22 , 23 , 24 ]. Are these all the reasons?…”
Section: Discussionmentioning
confidence: 99%
“…The sweet potato, as a low-nitrogen-tolerant crop, grows well in nitrogen-poor infertile soils. Previous studies have shown that the growth ability of the sweet potato is partially due to the functions of diazotrophic growth-promoting bacteria that contain endo- and epiphytic microorganisms of this plant [ 21 , 22 , 23 , 24 ]. Various endophytic bacteria were isolated from sweet potatoes [ 18 ], such as Azospirillum sp.…”
Section: Introductionmentioning
confidence: 99%